Pemanfaatan Media Pembelajaran Berbasis Game untuk Menunjang Kemampuan Literasi Numerasi Siswa Kelas V SDN 1 Kudu - Fatafani, Sherly Regita; Rozie, Fachrur (Jurnal Ilmiah Wahana Pendidikan, 2025)
Education is a crucial element in improving the quality of human resources, especially for building Indonesia's golden generation. Based on data from the Global Human Capital Report, the quality of education in Indonesia is relatively low, mostly due to a lack of interest in learning and low interest in literacy. This research aims to evaluate the effect of using game-based learning media on the literacy and numeracy abilities of class V students at SDN 1 Kudu. The research method used is descriptive quantitative with an experimental design. The research results showed a significant increase in students' literacy and numeracy skills after using game-based learning media. The results of the pretest and posttest analysis show that the posttest score is higher than the pretest. Data normality and homogeneity tests show that the data is normally and homogeneously distributed. Hypothesis testing shows that there is a significant influence of the use of game-based learning media on students' literacy and numeracy skills. This research supports previous literature which states that game-based learning media can increase students' interest in learning and activeness in learning.